Early ultrasound surveillance of newly-created haemodialysis arteriovenous fistula - Richards, J; Summers, D; Sidders, A; Knight, S; Pettigrew, G (Elsevier, 2024)
Introduction We assess if ultrasound surveillance of newly-created arteriovenous fistulas (AVFs) can predict non-maturation sufficiently reliably to justify randomised controlled trial (RCT) evaluation of ultrasound-directed salvage intervention. Methods Consenting adults underwent blinded fortnightly ultrasound scanning of their AVF after creation, with scan characteristics that predicted AVF non-maturation identified by logistic regression modelling. Results Of 333 AVFs created, 65.8% matured by 10 weeks. Serial scanning revealed that maturation occurred rapidly, whereas consistently lower fistula flow rates and venous diameters were observed in those that did not mature. Wrist and elbow AVF non-maturation could be optimally modelled from the week four ultrasound parameters alone, but with only moderate positive predictive values (wrist, 60.6% (95% CI 43.9 – 77.3); elbow, 66.7% (48.9 - 84.4)). Moreover, 40 (70.2%) of the 57 AVFs that thrombosed by week 10 had already failed by the week 4 scan, thus limiting the potential of salvage procedures initiated by that scan’s findings to alter overall maturation rates. Modelling of the early ultrasound characteristics could also predict primary patency failure at 6 months, but that model performed poorly at predicting assisted primary failure (those AVFs that failed despite a salvage attempt), partly because patency of at-risk AVFs was maintained by successful salvage performed without recourse to the early scan data. Conclusions Early ultrasound surveillance may predict fistula maturation, but is likely, at best, to result in only very modest improvements in fistula patency. Power calculations suggest that an impractically large number of participants (>1700) would be required for formal RCT evaluation.